An Analysis of The Language Variations of Luwunese Through Speech Acts (Fokus: Luwu, North Luwu, and East Luwu) - Surahim, Irsyam; Ramli, Aswadi (Jurnal Dieksis ID, 2023)
The main objectives of this research were to determine the differences of language variation in the use of regional language  especially  Luwu, North Luwu and East Luwu in South Sulawesi area. The descriptive qualitative research method was applied by the researcher. The research was conducted at Luwu, North Luwu and East Luwu. The researcher describes that variety of luwu, North Luwu and East Luwu. In this research the researcher using purposive sampling, the researcher observed and interviewed all of the respondents  who from Luwu, North Luwu, and East Luwu. The researcher used video recording and field notes to conduct observation. Respondents’ activities and attitudes social was captured on video. Meanwhile, the researcher used field notes to obtain more accurate data. Based on the observation that The language variation in Luwu were different with the language  North Luwu people and East Luwu, because the variation Luwu language has same the similarity language spoken Buginese people and near also from the land of Buginese are. There were several factors that caused language variations of Luwunese including internal factors such as self perception, perception of language, language difficulties , and external factors such as social judgment. The factors divided into three categories: linguistic factors, which cover linguistic difficulties, psychological factors, and environmental factors. As a result, it is suggested that the researcher and reader get to know more about the language variations of Luwunese. By becoming acquainted with the language variations of Luwunese, the people has to study about the language of variety, in order that can helping communicate with the  kind.